Pengaruh Transfer Pricing dan Profitabilitas terhadap Penghindaran Pajak Perusahaan Publik Sektor Pertambangan di Indonesia - Christy, Lovena; Julianetta, Vennecia; Excel, Alexander; Tantya, Fiorin; Kristiana, Stefanie; Salsalina, Ita (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This study was conducted to examine the effect of transfer pricing and profitability on tax avoidance. The independent variables used are transfer pricing and profitability. While the dependent variable is tax avoidance as measured by using the effective tax rate (ETR). The population in this study are all mining companies in the energy and raw material sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period. Determination of the sample using purposive sampling method and obtained a sample of 140 companies. The results of the study indicate that transfer pricing has a significant negative effect on tax avoidance. While profitability has a positive effect on tax avoidance